2015
DOI: 10.3174/ajnr.a4262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of White Matter Multiple Sclerosis Lesions on the Volume Estimation of 6 Brain Tissue Segmentation Methods

Abstract: BACKGROUND AND PURPOSE:The accuracy of automatic tissue segmentation methods can be affected by the presence of hypointense white matter lesions during the tissue segmentation process. Our aim was to evaluate the impact of MS white matter lesions on the brain tissue measurements of 6 well-known segmentation techniques. These include straightforward techniques such as Artificial Neural Network and fuzzy C-means as well as more advanced techniques such as the Fuzzy And Noise Tolerant Adaptive Segmentation Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Because of that, in an attempt to evaluate this effect, we generated a set of synthetic images as done in (Battaglini et al, 2012, Chard et al, 2010, Gelineau-Morel et al, 2012, Nakamura and Fisher, 2009) to evaluate the effect of the lesions on tissue segmentation. The effect of such lesions on automatic tissue segmentation strategies has been widely evaluated, and also strategies to reduce this effect, such as masking out the lesions or fill them before segmentation, have been proposed (Battaglini et al, 2012, Chard et al, 2010, Valverde et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Because of that, in an attempt to evaluate this effect, we generated a set of synthetic images as done in (Battaglini et al, 2012, Chard et al, 2010, Gelineau-Morel et al, 2012, Nakamura and Fisher, 2009) to evaluate the effect of the lesions on tissue segmentation. The effect of such lesions on automatic tissue segmentation strategies has been widely evaluated, and also strategies to reduce this effect, such as masking out the lesions or fill them before segmentation, have been proposed (Battaglini et al, 2012, Chard et al, 2010, Valverde et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The effect of lesions on total tissue volume was partly limited due to the canceling effect between the errors produced in normal-appearing tissue and the number of lesion voxels that were segmented as GM ( Valverde et al, 2015b ). This aspect is relevant because it explains why the observed % of error in total tissue volume was small or not significant between the evaluated pipelines of our study, even within the Original images intentionally segmented containing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing differences for a particular method in different studies may be influenced by the same image data, imaging hardware and acquisition parameters ( Clark et al, 2006 ). Furthermore, several authors have reported that the inclusion of WM lesions in tissue segmentation can affect significantly the accuracy of these techniques ( Battaglini et al, 2012 , Nakamura and Fisher, 2009 , Valverde et al, 2015b ), leading to the development of different preprocessing strategies to fill lesion regions with signal intensities similar to WM before tissue segmentation ( Battaglini et al, 2012 , Chard et al, 2010 , Valverde et al, 2014 ). So far, in all the lesion filling approaches, MS lesions have to be delineated first, usually by their manual annotation, which is a tedious, challenging and time-consuming task ( Sanfilipo et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…For automatically segmented lesions, the LST lesion filling module was used for in‐painting. The underlying algorithm of T1 lesion filling based on automatic T2 FLAIR lesion segmentation is inspired by a method proposed by Chard and colleagues, where candidate region voxels were replaced by random intensities from a Gaussian distribution generated from the normal‐appearing WM intensities and then filtered to reintroduce the original spatial variation in WM …”
Section: Methodsmentioning
confidence: 99%